The Feminine Touch in the Shaping of Modern Evolutionary Theory - Fernandez-Tapia, A (Journal of Social, Evolutionary, and Cultural Psychology, 2013)
This overview of women s contribution to evolutionary thought reflects on a few of the groundbreaking ethologists, anthropologists, and psychologists that prominently contributed and continue to influence my own understanding of evolutionary psychology. Inspired by the highly popular account of Fossey s fieldwork on the social behavior of gorillas, an overview of women studying relevant feminine adaptive issues as well as an account of women interpreting evolutionary theory from a feminine view are briefly presented. This review reveals that the challenge of introducing a feminine touch to evolutionary psychology is just beginning and promises to lead to an integrative view of the field with women in mind.